Does township tourism contribute to government's strategic goals for the tourism sector? : a case study of bed and breakfast entrepreneurs in Gugulethu and Langa, Cape Town - Joseph, Hilary (Department of Sociology, 2015)
The purpose of the study was to address the question: Does Township Tourism contribute to the South African government's strategic goals for the tourism sector? A qualitative case study was done in the two Cape Town townships, Gugulethu and Langa to identify and interview a number of Township Tourism Entrepreneurs (TTEs). Selected works of C.M. Rogerson are used as a framework to compare these TTEs, to those studied in a number of other townships in South Africa. Rogerson described TTEs as having identified an economic opportunity and categorised them as Opportunistic Entrepreneurs, who share numerous qualities with white Lifestyle Entrepreneurs, such as being approximately 50 years old, predominantly females, who use their own funding to start accommodation businesses in picturesque rural towns, as a second career or income generator. The study has 5 TTEs in the sample, which is a convenient sample drawn from Cape Town Tourism ' s membership list of 14 members who are operating accommodation businesses in these areas. In-depth interviews were conducted with five TTEs, a senior staff member from the City of Cape Town Tourism Department, another from the Provincial Destination Marketing Organization and one tour operator. Informal discussions were held with staff at the Tourism visitors centres in Langa and Gugulethu and other tourism stakeholders prior to doing the interviews. The study also drew on multiple data sources, including policy documents. The study explored the TTEs' motivations for starting their accommodation businesses, and looked at how they conform to the entrepreneurial characteristics and categorisation given by Rogerson and the Global Entrepreneur Monitor Report, i.e. Survivalist/Opportunistic/Lifestyle Entrepreneurs. The study explores how this categorisation aligns TTEs with the vision and goals for the sector that policymakers and government have set, and whether this enables them to access the appropriate support. The findings suggest that TTEs should not all be assumed to have business growth as a primary goal, and that a number could be categorised as Lifestyle Entrepreneurs rather than Opportunistic Entrepreneurs, albeit in an urban township setting. This study also suggests that township Lifestyle Entrepreneurs have a key function in the tourism sector and consideration should be given to place them in a form of clustering with opportunistic high growth entrepreneurs. This would enhance this sector's contribution to the ambitious goals set for tourism as a transformation, job creation, and poverty alleviation tool.